Topical hepatic hypothermia associated with ischemic preconditioning. Histopathological and biochemical analysis of ischemia reperfusion damage in a 24 hour model - Gabiatti,Gémerson (2018)
Abstract Purpose: To develop a new 24 hour extended liver ischemia and reperfusion (LIR) model analyzing the late biochemical and histopathological results of the isolated and combined application of recognized hepatoprotective mechanisms. In addition, we used a new stratification with zoning to classify the histological lesion. Methods: A modified animal model of severe hepatic damage produced through 90 minutes of segmental ischemia (70% of the organ) and posterior observation for 24 hours of reperfusion, submitted to ischemic preconditioning (IPC) and topical hypothermia (TH) at 26ºC, in isolation or in combination, during the procedure. Data from intraoperative biometric parameters, besides of late biochemical markers and histopathological findings, both at 24 hours evolution time, were compared with control (C) and normothermic ischemia (NI) groups. Results: All groups were homogeneous with respect to intraoperative physiological parameters. There were no losses once the model was stablished. Animals subjected to NI and IPC had worse biochemical (gamma-glutamyl transpeptidase, alkaline phosphatase, lactate dehydrogenase, aspartate aminotransferase, alanine aminotransferase, direct bilirubin, and total bilirubin) and histopathological scores (modified Suzuki score) compared to those of control groups and groups with isolated or associated TH (p < 0.05). Conclusion: The new extended model demonstrates liver ischemia and reperfusion at 24 hour of evolution and, in this extreme scenario, only the groups subjected to topical hypothermia, combined with ischemic preconditioning or alone, had better outcomes than those subjected to only ischemic preconditioning and normothermic ischemia, reaching similar biochemical and histopathological scores to those of the control group.